Binder-free NiCoFe layered double hydroxide nanosheets for flexible energy storage devices with high-rate-retention characteristics. (10th July 2021) - Ni, Chung-Sheng; Liu, Shih-Fu; Lee, Jyh-Fu; Pao, Chih-Wen; Chen, Jeng-Lung; Chen, Han-Yi; Huang, Jin-Hua
Highlights: NiCoFe LDH exhibits 727 c g   −   1 at 1 a g   −   1 and 77% capacity retention at 50 a g   −   1 . It provides 87% capacity retention after 10, 000 cycles. The mechanism of rate retention improvement is studied by in-operando XANES. The NiCoFe-LDH based energy storage devices show great flexibility. The NiCoFe-(1:2:0.1) layered double hydroxide as an efficient electrode material for the hybrid energy storage devices by operando XANES analyses. Abstract: In this study, NiCoFe layered double hydroxide (LDH) nanosheets with various composition ratios are synthesized via a simple electrodeposition method. The NiCoFe LDH prepared with a precursor molar ratio of Ni:Co:Fe = 1:2:0.1 shows the best performance with a specific capacity of 727 C g   −   1 at 1 A g   −   1, a high rate retention of 77% at 50 A g   −   1, and a capacity retention of 87% after 10, 000 cycles. The quick in-operando X-ray absorption study shows that the electrochemical activity of the various LDHs mainly originates from the change in the valence state of Ni ions, and the Fe ions improve the rate capability as well as the cycling stability. Furthermore, a solid-state energy storage device is fabricated using the NiCoFe-(1:2:0.1) LDH as the positive electrode, commercial activated carbon as the negative electrode, and PVA-KOH as the electrolyte. The device exhibits an energy density of 8.7 Wh kg −1 at 62.8 W kg −1 and 6.8 Wh kg −1 at 3139.2 W kg −1 . The cycling stabilities of the device under folding and unfolding conditions are also evaluated, and the performances are found about the same, revealing great potential for flexible energy storage applications. Graphical abstract: Image, graphical abstract The NiCoFe-(1:2:0.1) layered double hydroxide as an efficient electrode material for the hybrid energy storage devices by operando XANES analyses.